RELATIONSHIP BETWEEN SUBJECTIVE WELL-BEING AND COMMITMENT TO SUCCESS OF STUDENTS - Hakobyan , N.M. (Modern Psychology, 2022)
The aim of the study is to investigate the relationship between subjective well-being and the pursuit of success in junior and senior students. The results show that the highest indicators of subjective well- being of students are expressed in the scales of peace, health, happiness, existence, which is obviously related to the current situation in Armenia caused by the war in Artsakh and the coronavirus pandemic. Psychological, physical and mental well-being among students is preferable to social and material well-being. Students are highly motivated to succeed in achieving the desired goal. Senior students, unlike undergraduate students, are more satisfied with all aspects of life. Senior students are more motivated to succeed than junior students. Students with a high level of success motivation have a higher level of life satisfaction.